2019
DOI: 10.1093/ajcn/nqy327
|View full text |Cite
|
Sign up to set email alerts
|

Carbon footprint of self-selected US diets: nutritional, demographic, and behavioral correlates

Abstract: Background A substantial portion of greenhouse gas emissions (GHGE) has been attributed to the food sector, but little is known about the association between the carbon footprint of individual self-selected diets in the United States and nutritional quality. Objectives The aims of this study were to assess the GHGE from individual self-selected diets in the United States and examine their association with nutritional quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
85
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(115 citation statements)
references
References 31 publications
13
85
2
1
Order By: Relevance
“…In our study, reduced dietary carbon footprint over time was associated with both more healthy and unhealthy food choices. In line with previous studies 25,[28][29][30] , our results suggest that increased consumption of unhealthy choices such as sweets and snacks correlates with lower dietary carbon footprint. This finding and the call for reduced intake of animal-based foods have raised concerns regarding the nutritional adequacy of diets mainly designed to reduce the dietary carbon footprint.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, reduced dietary carbon footprint over time was associated with both more healthy and unhealthy food choices. In line with previous studies 25,[28][29][30] , our results suggest that increased consumption of unhealthy choices such as sweets and snacks correlates with lower dietary carbon footprint. This finding and the call for reduced intake of animal-based foods have raised concerns regarding the nutritional adequacy of diets mainly designed to reduce the dietary carbon footprint.…”
Section: Discussionsupporting
confidence: 92%
“…This hypothesis is supported by results from a national food survey in Sweden showing that individuals with median or above median income more often consume animal-based products compared to individuals with below median income 14 . However, other studies have not found any association between dietary carbon footprint and educational level 30 . Like previous studies 30 , our results show that dietary carbon footprint was higher for men than women also for the same amount of calories, indicating men as an important target group for policy instruments aiming to reduce climate impact from diets.…”
Section: Discussionmentioning
confidence: 88%
“…This limitation prevented a time trend analysis, and required that the same food-specific waste proportions were applied consistently to FAH and FAFH. Furthermore, this limitation made it necessary to apply food-specific waste proportions consistently to all individuals in NHANES, which has precedent in previous studies [6,[36][37][38]. The need to develop innovative methods to merge these datasets, and the additional limitations of doing so, have been noted elsewhere [39].…”
Section: Discussionmentioning
confidence: 99%
“…8,9 All these studies contributed to our existing knowledge about diet and climate; however, most used aggregate diets, which miss the nuance seen in the wide variation in GHGE of self-selected diets. [10][11][12] By working with a single datapoint (ie, a national average), these studies were unable to assess which individuals might be receptive to making changes and, ultimately, how policies might be better targeted to induce such changes.…”
Section: Introductionmentioning
confidence: 99%